The Influence of Transformational Leadership and Self-Efficacy Toward Teachers’ Organizational Commitment - Susilawati, Susilawati; Setyaningsih, Sri; Sunaryo, Widodo (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
The objective of this study is to analyze the impact of transformational leadership and self-efficacy on the commitment of private Madrasah Aliyah teachers in Bekasi City, West Java, to their organization. In this study, the researcher used the quantitative approach through the survey method. The population of this study comprised private Madrasah Aliyah teachers in Bekasi city, with a total of 383 teachers. The sampling technique employed a multistage random sampling design, encompassing 113 teachers. In this study, the primary data were obtained from the teachers of Madrasah Aliyah in Bekasi City. The data was collected by the result of the questionnaires (2 independent variables: transformational leadership variable and self-efficacy, and one dependent variable: organizational commitment), which were distributed to them. The data presented herein were collected through the implementation of a survey method that incorporated a questionnaire. The data analysis techniques employed in this study encompassed the use of descriptive statistics and quantitative analysis. The hypothesis testing employed in this study involved the implementation of multiple linear regression tests. The findings of this study demonstrate that transformational leadership exerts a substantial influence on commitment to the teacher organization, with a statistical significance value of 0.000 <0.05. Secondly, the findings indicate that self-efficacy has a substantia0.05. Thirdly, the findings of this study demonstrate a substantial relationship between transformational leadership and self-efficacy on commitment to the teacher organization, as evidenced by an adjusted R-squared value of 0.367.